Analisis Kelayakan Implementasi Titik Akses Virtual (VAP) sebagai Solusi Efisiensi Infrastruktur Jaringan untuk Usaha Mikro, Kecil, dan Menengah (UMKM) dari Perspektif Tekno-Ekonomi - Indah Ratu Aulia; Nyoman Bogi Aditya Karna; Sofia Naning Hertiana (Universitas Stikubank, 2026)
Micro, Small, and Medium Enterprises (MSMEs) often face network infrastructure inefficiencies due to fragmented management and budget constraints. This study aims to analyze the feasibility of implementing Virtual Access Point (VAP) technology as a solution for network infrastructure efficiency in MSME shop clusters. Using a hybrid simulation approach, this study compares the performance between conventional infrastructure (Scenario A) and VAP-based integrated infrastructure (Scenario B). Technical evaluations were conducted using UniFi Design Center for signal propagation analysis and GNS3 for logical topology and network security validation. Economic analysis was performed using the Total Cost of Ownership (TCO) and Return on Investment (ROI) methods. The results showed that Scenario B was able to eliminate Co-Channel Interference, maintain signal stability in the range of -60 dBm to -65 dBm, and ensure data isolation between tenants through the IEEE 802.1Q (VLAN) protocol. From an economic perspective, the implementation of VAP reduces initial investment costs (CAPEX) by 32% and operational costs (OPEX) by 21.6% per year. With an ROI value of 102.36% and a payback period of 5.9 months, VAP technology has proven to be highly feasible as an efficient, secure, and profitable standard solution for MSME network infrastructure.